2015
DOI: 10.15835/nbha.43.1.9793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt and Water Stress on Plant Growth and on Accumulation of Osmolytes and Antioxidant Compounds in Cherry Tomato

Abstract: The effects of salt and water stress on growth and several stress markers were investigated in cherry tomato plants. Some growth parameters (stem length and number of leaves) and chlorophyll contents were determined every third day during plant growth, and leaf material was collected after 25 and 33 days of treatment. Both stresses inhibited plant growth; chlorophyll levels, however, decreased only in response to high NaCl concentrations. Proline contents largely increased in leaves of stressed plants, reachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
1
17
1
Order By: Relevance
“…It has been observed that higher levels of salinity cause generation of ROS. In the present investigation, presence of NaCl enhanced the level of TBARS [20] and lowered the activities of antioxidant enzymes in genotype Queen, whereas, lower TBARS and higher activities of antioxidant enzymes were noticed in genotype BL-1076. Thus, it is clear that genotype Queen was sensitive while BL-1076 was tolerant to the NaCl stress.…”
Section: Effect Of Salt Stress On Growth Attributes Of Ten Genotypes contrasting
confidence: 42%
“…It has been observed that higher levels of salinity cause generation of ROS. In the present investigation, presence of NaCl enhanced the level of TBARS [20] and lowered the activities of antioxidant enzymes in genotype Queen, whereas, lower TBARS and higher activities of antioxidant enzymes were noticed in genotype BL-1076. Thus, it is clear that genotype Queen was sensitive while BL-1076 was tolerant to the NaCl stress.…”
Section: Effect Of Salt Stress On Growth Attributes Of Ten Genotypes contrasting
confidence: 42%
“…These results are in agreement with AL Hassan et al (2015), who described a significant reduction of chlorophyll a and b in six wheat cultivars and soybean. According to AL Hassan et al (2015), salt stress also decreased the chlorophyll levels in plants which was due to the inhibition of chlorophyll biosynthesis, besides activating its degradation by the cholorophyllase enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…For example, osmotic stress in the initial stage of salinity stress in wheat (Triticum aestivum) caused various physiological changes, such as the interruption of membranes, nutrient imbalance, and impaired ability to detoxify reactive oxygen species, differences in antioxidant enzymes, decreased photosynthetic activity, and a decrease in stomatal opening [4]. In cherry tomato (Lycopersicon esculentum), high salinity decreased the concentration of leaf proteins, total carotenoids, chlorophyll, soluble sugars, and starch and phenolic contents [5]. With the increase in uptake of sodium (Na + ) and chlorine (Cl − ), the nitrogen (N), calcium (Ca 2+ ), and potassium (K + ) concentration and with the decreased in Mg 2+ concentration, the nutritional balance of the plants is upset, which ultimately reduces their growth [6].…”
Section: Introductionmentioning
confidence: 99%